The visual perception of projectile trajectories and the guidance of interceptive behaviour - Reed, N (2002)
﻿ Experiments were conducted examining human interception of projectiles. It was found that fielders tend not maintain a linear optic trajectory (LOT) as advocated by McBeath, Shaffer, and Kaiser (1995) for interception in two-dimensions. Furthermore, it was shown that its curvature provided an ambiguous cue to action. New interception models were proposed based on optic acceleration cancellation (OAC) and the constant δ model significantly improved upon the performance of the LOT model. Awareness of interception strategy was investigated by questioning subjects about their angle of gaze variation during the ball flight. A lack of awareness of the critical information that guides interceptive behaviour was demonstrated. It is proposed that the information is stored implicitly, challenging the position of Shanks and St. John (1994). Subjects were asked to discriminate the visual information that they experienced before running to catch real balls to examine the validity of experiments that test human ability to discriminate the acceleration of simulated trajectories. Discriminative performance found to remain high even when the duration of viewed information is reduced. This intact discriminative ability led to the suggestion that trajectory discrimination occurs very rapidly after ball launch. The movement and gaze angle of fielders running to catch under conditions in which OAC cannot be sustained was analysed. Subjects showed little deviation from the strategy until the final moments of the catch. The overall conclusion to the thesis is that subjects react rapidly to the optic acceleration of a projectile to determine interceptive behaviour but may not be aware of the sensory basis of their decision and use an approximate version of the constant δ strategy to reach the interception point.